Basic process engineering control - Agachi, Paul Șerban; Cristea, Mircea Vasile, 1961- (De Gruyter textbook., 2014)
This book provides methods, problems and tools used in process control engineering. It discusses: process knowledge, sensor system technology, actuators, communication technology and logistics as well as design and construction of control systems and their operation. The knowledge goes beyond the traditional process engineering field by applying the same principles to biomedical processes, energy production and management of environmental issues.